2014
DOI: 10.17219/acem/37233
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Self Report Version of the Leeds Assessment of Neuropathic Symptoms and Signs Score for Identification of Neuropathic Pain in Patients from Northern Turkey*

Abstract: Background. Diagnosis and treatment of neuropathic pain is an important clinical problem. Objectives. A self report version of the Leeds Assessment of Neuropathic Symptoms and Signs (S-LANSS) score provides identification of neuropathic pain without the help and need of a clinician. We targeted validation of the S-LANSS score in the nothern Turkish population in this study. Material and Methods. For the linguistic validation of S-LANSS, translation and back-translation method was used to adapt S-LANSS into Tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
(15 reference statements)
0
9
1
Order By: Relevance
“…Previous studies have found the sensitivity and specificity of s-LANSS to identify neuropathic pain in myriad chronic pain conditions to range between 22% and 98%, and 69% and 97%, respectively; for painDETECT, the sensitivities and specificities have ranged between 64% and 93%, and 53% and 80%, respectively. 11,[19][20][21][22] Although painDETECT has not been validated to detect "mixed" or even nociceptive pain, previous studies have found mean scores for "mixed" conditions to be intermediate between neuropathic and nonneuropathic pain and to fall within the "possible neuropathic pain" category 23 ; therefore, to align all 3 designation systems, we considered intermediate scores between likely and unlikely neuropathic pain to denote a "mixed" condition. All instrument scoring was performed by an investigator blinded to physician-rendered pain designation and clinical information.…”
Section: Classification Of Neck Painmentioning
confidence: 99%
“…Previous studies have found the sensitivity and specificity of s-LANSS to identify neuropathic pain in myriad chronic pain conditions to range between 22% and 98%, and 69% and 97%, respectively; for painDETECT, the sensitivities and specificities have ranged between 64% and 93%, and 53% and 80%, respectively. 11,[19][20][21][22] Although painDETECT has not been validated to detect "mixed" or even nociceptive pain, previous studies have found mean scores for "mixed" conditions to be intermediate between neuropathic and nonneuropathic pain and to fall within the "possible neuropathic pain" category 23 ; therefore, to align all 3 designation systems, we considered intermediate scores between likely and unlikely neuropathic pain to denote a "mixed" condition. All instrument scoring was performed by an investigator blinded to physician-rendered pain designation and clinical information.…”
Section: Classification Of Neck Painmentioning
confidence: 99%
“…Demographic characteristic of eight studies included using LANSS instrument in assessment of neuropathic pain (Table 1). Eight (8) studies [20,24,[28][29][30][31][32][33] were included in this review. Two studies each were reported in the Greek [28,30] and Turkish languages [32,33].…”
Section: Lanss Description Of the Lanss Articlesmentioning
confidence: 99%
“…Eight (8) studies [20,24,[28][29][30][31][32][33] were included in this review. Two studies each were reported in the Greek [28,30] and Turkish languages [32,33]. Each of the following languages reported one study -Brazilian Portuguese [31], Korean [20], Spanish [24] and Portuguese [29].…”
Section: Lanss Description Of the Lanss Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Questionnaires are being developed to try to identify the qualities of neuropathic pain. 13 , 14 At present, the scales of LANSS, NPQ and ID Pain are commonly used with high sensitivity and specificity. The accuracy, specificity, sensitivity, positive and negative predictive value of three scales have been compared in a study.…”
Section: Introductionmentioning
confidence: 99%